(untitled) (Journal of Media studies, 2020)
SWOT analysis is a method widely used in analyzing theinternal and external environments of organization in enterprise management.From the perspective of educational management, this article discusses thetheoretical basis of applying SWOT analysis in private kindergartens and thefeasibility of its application; by case studies, this article explores the scope,procedure, function and issues need to be addressed of SWOT analysis, revealsthe position and role of SWOT analysis in private kindergarten management, andexplores a new idea and method for private kindergarten management.